An international comparison of THA patients, implants, techniques, and survivorship in Sweden, Australia, and the United States. (4th March 2019) - Paxton, Elizabeth W; Cafri, Guy; Nemes, Szilard; Lorimer, Michelle; Kärrholm, Johan; Malchau, Henrik; Graves, Stephen E; Namba, Robert S; Rolfson, Ola
Abstract : Background and purpose — International comparisons of total hip arthroplasty (THA) practices and outcomes provide an opportunity to enhance the quality of care worldwide. We compared THA patients, implants, techniques, and survivorship in Sweden, Australia, and the United States. Patients and methods — Primary THAs due to osteoarthritis were identified using Swedish (n = 159, 695), Australian (n = 279, 693), and US registries (n = 69, 641) (2003–2015). We compared patients, practices, and implant usage across the countries using descriptive statistics. We evaluated time to all-cause revision using Kaplan–Meier survival curves. We assessed differences in countries' THA survival using chi-square tests of survival probabilities. Results — Sweden had fewer comorbidities than the United States and Australia. Cement fixation was used predominantly in Sweden and cementless in the United States and Australia. The direct anterior approach was used more frequently in the United States and Australia. Smaller head sizes (≤ 32 mm vs. ≥ 36 mm) were used more often in Sweden than the United States and Australia. Metal-on-highly cross-linked polyethylene was used more frequently in the United States and Australia than in Sweden. Sweden's 5- (97.8%) and 10-year THA survival (95.8%) was higher than the United States' (5-year: 97.0%; 10-year: 95.2%) and Australia (5-year: 96.3%; 10-year: 93.5%). Interpretation — Patient characteristics, surgical techniques, and implants differed across the 3 countries, emphasizing the need to adjust for demographics, surgical techniques, and implants and the need for global standardized definitions to compare THA survivorship internationally.